MicroRNAs 29b and 181a down‐regulate the expression of the norepinephrine transporter and glucocorticoid receptors in PC12 cells. (22nd September 2016) - Deng, Maoxian; Tufan, Turan; Raza, Muhammad U.; Jones, Thomas C.; Zhu, Meng‐Yang
Abstract: MicroRNAs are short non‐coding RNAs that provide global regulation of gene expression at the post‐transcriptional level. Such regulation has been found to play a role in stress‐induced epigenetic responses in the brain. The norepinephrine transporter (NET) and glucocorticoid receptors are closely related to the homeostatic integration and regulation after stress. Our previous studies demonstrated that NET mRNA and protein levels in rats are regulated by chronic stress and by administration of corticosterone, which is mediated through glucocorticoid receptors. Whether miRNAs are intermediaries in the regulation of these proteins remains to be elucidated. This study was undertaken to determine possible regulatory effects of miRNAs on the expression of NET and glucocorticoid receptors in the noradrenergic neuronal cell line. Using computational target prediction, we identified several candidate miRNAs potentially targeting NET and glucocorticoid receptors. Western blot results showed that over‐expression of miR‐181a and miR‐29b significantly repressed protein levels of NET, which is accompanied by a reduced [ 3 H] norepinephrine uptake, and glucocorticoid receptors in PC12 cells. Luciferase reporter assays verified that both miR‐181a and miR‐29b bind the 3′UTR of mRNA of NET and glucocorticoid receptors. Furthermore, exposure of PC12 cells to corticosterone markedly reduced the endogenous levels of miR‐29b, which was not reversed by the application of glucocorticoid receptor antagonist mifepristone. These observations indicate that miR‐181a and miR‐29b can function as the negative regulators of NET and glucocorticoid receptor translation in vitro . This regulatory effect may be related to stress‐induced up‐regulation of the noradrenergic phenotype, a phenomenon observed in stress models and depressive patients. This study demonstrated that miR‐29b and miR‐181a, two short non‐coding RNAs that provide global regulation of gene expression, markedly repressed protein levels of norepinephrine (NE) transporter and glucocorticoid receptor (GR), as well as NE uptake by binding the 3′UTR of their mRNAs in PC12 cells. Also, exposure of cells to corticosterone significantly reduced miR‐29b levels through a GR‐independent way. Abstract : This study demonstrated that miR‐29b and miR‐181a, two short non‐coding RNAs that provide global regulation of gene expression, markedly repressed protein levels of norepinephrine (NE) transporter and glucocorticoid receptor (GR), as well as NE uptake by binding the 3′UTR of their mRNAs in PC12 cells. Also, exposure of cells to corticosterone significantly reduced miR‐29b levels through a GR‐independent way.